Characterization of betel vine (piper betle L) types of Malappuram District - Preethy T T (Department of Plant Breeding and Genetics, College of Horticulture, 2012)
The present investigation on “Characterization of betel vine (Piper betle L.) types of Malappuram district” was carried out at the Department of Plant Breeding and Genetics, College of Horticulture, KAU, Vellanikkara and farmer’s field in Malappuram district during 2013 – 2014 aiming to study the diversity of betel vine types in Tirur and nearby areas of Malappuram district and to characterize the types based on morphological and biochemical features. Puthukodi, Chelan, Karinadan and Nadan were the betel vine cultivars recorded from Malappuram District. Puthukodi and Nadan were the most common cultivars whereas Chelan and Karinadan were the cultivars conserved by few farmers. Morphological characterization revealed distinctness of Karinadan and Chelan from other cultivars. Karinadan had dark green leaves with even leaf margin, short petiole, mostly ovate lanceolate leaf lamina, high brittleness and medium pungency. Leaf characters including leaf length, leaf width, leaf area and leaf weight per unit area were comparatively high in this cultivar. Orthotropic shoots of this cultivar showed uniform purple – green color. It produced hanging lateral branches. The plant growth parameters like plant height, total number of leaves, number of lateral branches and number of leaves per lateral branch were significantly low in this cultivar. On the other hand, Chelan had light green leaves with wavy leaf margin, long petiole, ovate leaf lamina and round leaf base. Leaf characters including leaf length, leaf width, leaf area and leaf weight per unit area and brittleness were significantly low in this cultivar leading to low market preference. In this cultivar, internodes of orthotropic shoots showed light green colour with purple tinge. Lateral branches of Chelan were semierect in nature. The plant growth parameters like plant height, total number of leaves, number of lateral branches and number of leaves per lateral branch were significantly high in this cultivar, resulting in higher number of leaves per plant. Nadan, Puthukodi and Muvattupuzha Local cultivars had green leaves with even margin and medium brittleness. Puthukodi recorded maximum leaf weight per unit area and optimum leaf parameters, making it as the most preferred cultivar in Malappuram district. Profuse flowering was observed in all cultivars during the study period. Chelan was identified as male cultivar and all others were female cultivars. Spikes produced on Chelan were long, slender with short peduncle. Female cultivars produced medium lengthy spikes having medium diameter. Spikes were axillary and opposite to leaf. Sessile naked florets were compactly arranged on the inflorescence axis. A bract subtended each floret, both in male and female spikes. Female spike was very distinguishable with the presence of 6 - 9 white coloured sessile stigmatic lobes on each floret. Male spikes were yellow in color and at the stage of anthesis, two black stamens protruded from each floret protruded. Essential oil content was maximum in Muvattupuha Local, a cultivar with high pungency and it was low in Chelan. GC studies revealed that, eugenol was the major component of essential oil in all cultivars with high content (20.80 per cent) in Chelan. Possible compounds identified from the chromatograms of oil from different cultivars were hydroxychavicol, β caryophyllene and 5-(2-propenyl)-1, 3- benzodioxole. Karinadan was rich in biochemical constituents whereas Chelan was significantly low in biochemical constituents. Puthukodi with optimum leaf characters recorded medium pungency. Studies on genetic parameters revealed that most of the characters were less affected by environmental factors. Many of the characters under study showed high heritability with high genetic gain, indicating additive gene effects and selection must be effective. Correlation studies showed that the highest significant positive genotypic correlation of total number of leaves was with number of leaves per lateral branch followed by plant height and number of lateral branches. Number of leaves per lateral branch showed highest positive direct effect and all other characters showed negative direct effect on total number of leaves. The dendrogram based on Euclidean distance proved that Chelan was very distinct from other cultivars under study. Karinadan also formed a separate cluster with a Euclidean distance of 1650.58 from Muvattupuzha Local. Nadan and